Impaired Digit Span Can Predict Further Cognitive Decline In Older People With Subjective Memory Complaint: A Preliminary Result - Kurt, Pınar; Yener, Görsev; Oğuz, Meral (Routledge Journals, Taylor & Francis Ltd, 4 Park Square, Milton Park, Abingdon Ox14 4Rn, Oxfordshire, England, 2011)
Subjective memory complaint (SMC) is common among elderly people, and is thought to be part of mild cognitive impairment (MCI). We evaluated whether impaired digit span (IDS) in older people with SMC can predict wider impairment in future neuropsychological tests that correspond to MCI. After a mean of 6.6 years from the initial assessment, we reevaluated 16 subjects with SMC and normal digit span (NDS) scores (mean age 57.6 +/- 8.1 years) and 28 subjects with SMC and IDS scores (mean age 59.7 +/- 9.9 years). The IDS group showed wider cognitive decline in tests of short-term verbal memory and category verbal fluency compared to the NDS group. IDS scores indicate an earlier step for conversion of SMC to MCI.
Keywords: subjective memory complaint; Mild Cognitive İmpairment; Digit Span; Alzheimers-Disease; Risk-Factors; Dementia; Association; Sübjektif Bellek Şikayet; Hafif Kognitif Bozukluk; Sayı Dizisi; Alzheimer Hastalığı; Risk Faktörleri; Bunaklık; dernek